Safety and tolerability review of lorcaserin in clinical trials. Issue 5 (14th September 2016) - Greenway, F. L.; Shanahan, W.; Fain, R.; Ma, T.; Rubino, D.
Summary: Lorcaserin is a novel selective serotonin 2C receptor agonist indicated by the US Food and Drug Administration for chronic weight management in adults with obesity or overweight with ≥1 comorbidity. The safety and efficacy of lorcaserin were established during two Phase III clinical trials in patients without diabetes (BLOOM and BLOSSOM) and one Phase III clinical trial in patients with type 2 diabetes (BLOOM‐DM). Headache was the most common adverse event experienced by patients during all Phase III trials. Additional adverse events occurring in >5% of patients receiving lorcaserin included dizziness, fatigue, nausea, dry mouth and constipation in patients without diabetes, and hypoglycaemia, back pain, cough and fatigue in patients with diabetes. In a pooled analysis of echocardiographic data collected during the three lorcaserin Phase III trials, the incidence of FDA‐defined valvulopathy was similar in patients taking lorcaserin and the placebo. Here, the safety profile of lorcaserin at the FDA‐approved dose of 10 mg twice daily is reviewed using data from the lorcaserin Phase III programme, with a focus on theoretical adverse events commonly associated with agonists of the serotonin receptor family. Based on the lorcaserin Phase III clinical trial data, lorcaserin is safe and well tolerated in the indicated patient populations.